Síntese De Zeólitas A Partir De Resíduos De Rochas Ornamentais, Modificadas Com Nb2O5/SO42-, E Aplicação Como Catalisador Para Síntese De Biodiesel - Céleri, Eliomar Pivante (2024)
Brazil stands out as a major producer of ornamental rocks, with the state of Espírito Santo making a significant contribution by producing approximately 80% of this type of rock in the country. However, this production generates waste that requires management to mitigate environmental impacts. In this study, ornamental rock waste was used for the first time to synthesize zeolites. The waste consisted of quartz and potassium feldspars, albite, and orthoclase. Due to the mineralogical composition, the alkaline fusion method was employed to destroy the crystalline structure and obtain reactive aluminosilicates for zeolite crystallization. Crystallization took place in polyethylene flasks at 95°C for 48 hours. The results showed that, in just 6 hours of crystallization, LTA zeolites were obtained with over 99% crystallinity. After 48 hours, LTA zeolites were converted into SOD zeolites. The SOD zeolite was modified with sulfated niobium oxide, presenting a surface area of approximately 19 m2 .g-1 , pore volume of 0.076 cm3.g-¹ , and most frequent pore diameter of 3.360 nm, classified as mesoporous. LTA, SOD, and modified SOD zeolites were tested as catalysts for the transesterification of soybean oil and esterification of fatty acids for biodiesel production. Different alcohols (methanol, ethanol, butanol, and isoamyl alcohol) were used for synthesis, varying reaction parameters such as time (2 to 12 hours), temperature (60 to 100°C), and alcohol-to-oil ratio (10:1 to 25:1). Although pure SOD zeolite showed no catalytic activity for biodiesel synthesis from esterification and transesterification reactions, modification with Nb2O5/SO4²- resulted in 12% conversion for biodiesel synthesis by transesterification and 52% by esterification. Among the catalysts studied, the trend for better catalytic activity was observed for Nb2O5/SO4²- > SOD/Nb2O5/SO4²- > Nb2O5 > LTA zeolite > SOD zeolite. Finally, this study demonstrates the feasibility of using ornamental rock waste in zeolite synthesis, paving the way for innovative and sustainable applications.